Latency Aware Workload Offloading in the Cloudlet Network - Xiang Sun; Ansari, Nirwan (IEEE communications letters, 2017)
We propose a novel network architecture by leveraging the cloudlet concept, the software defined networking technology, and the cellular network infrastructure to bring the computing resource to the mobile edge. In order to minimize the average response time for mobile users (MUs) in offloading their application workloads to the geographically distributed cloudlets, we propose the latency-aware workload offloading (LEAD) strategy to allocate MUs' application workloads into suitable cloudlets. Simulation results demonstrate that LEAD incurs the lowest average response time as compared with two other existing strategies.